Can first aid training encourage individuals' propensity to act in an emergency situation? A pilot study. Issue 6 (28th June 2013) - Oliver, Emily; Cooper, Jane; McKinney, David
Abstract : Objective: To explore the effect that different activities included in first aid training can have on an individual's propensity to act in a medical emergency. Design: Additional pilot-developed activities were added to a core first aid training session to create six unique groups, including a control group where no activities were added. Participants rated their agreement to pre-identified fears following the course and scored their self-efficacy and willingness to act before, immediately after and 2 months after the course. Change values were compared between groups. Setting: Three locations in the UK (community halls, schools). Participants: 554 members of the public were recruited using advertising and community groups. A deliberately broad demographic was sought and achieved using targeted approaches where a particular demographic was deficient. Intervention: Each participant attended one British Red Cross first aid course lasting 2 h. Main outcome measures: The same questionnaire was completed by all participants before and after each course. Two months later all participants were asked a series of follow-up questions. Results: All courses showed an increase in self-efficacy and willingness to act immediately following the course. The course, which included both factual information relevant to helping in an emergency and 'helper' identity activities, produced significantly more positive responses to pre-identified fears. Conclusions: Activities which allow the learner to explore and discuss behaviour in an emergency situation can effectively increase the learner's propensity to act. First aid education should be expanded to support the learner to develop both the skill and the will to help.